Tangible and Natural Of Indonesian Cultural Heritage Presented In English Textbooks For Senior High School Student - Trifonia Fahik; Ni Made Ratminingsih (JSHP : Jurnal Sosial Humaniora dan Pendidikan, 2020)
Cultural elements play an essential role in learning a foreign language; thus, it is unavoidable that EFL (English Foreign Language) textbooks carry cultural elements. This study was framed with qualitative research and aim to explore the presence of intangible and tangible cultural heritage in the visual materials (painting, photography, drawing, digital drawing) and to examine their distribution according to their types. The data to be analyzed was obtained from two textbooks for senior high school students entitled English Skills for Better Future for grade tenth and eleventh in senior high school. Content analysis was applied to analyze types of visual materials that present cultural heritage. The result showed that 163 visuals material were determined as 84 photos, 14 digital drawings, nine brochures, 35 advertisements, four flyers, nine forms, 16 proverbs, and one riddle. Cultural bias and stereotypes have not been detected in the images presented in both textbooks with the same title for 10th and 11th grade students in senior high school. The images presented are suitable for students at the senior high school level. Visual has an aesthetic value and aims to bring students to know the various Indonesian culture elements presented in these textbooks. Teachers and students who use books published by PT Grafindo Medika Pratama as a learning resource, this study might help in mapping the type of culture presented in the textbooks.Keywords: Indonesian, cultural, heritage, visual, textbookAbstrakUnsur budaya memainkan peran penting dalam mempelajari bahasa asing; Dengan demikian, tidak dapat dipungkiri bahwa buku teks EFL (Bahasa Asing Inggris) mengandung unsur budaya. Dibingkai dengan penelitian kualitatif, penelitian ini bertujuan mengeksplorasi keberadaan warisan budaya berwujud benda dan tak benda yang disajikan dalam bentuk gambar (lukisan, fotografi, gambar, gambar digital) dan mengkaji sebarannya menurut jenisnya. Data yang akan dianalisis diperoleh dari dua buku siswa yang berjudul English Skills for the Future. Kedua buku ini digunakan oleh siswa kelas sepuluh dan sebelas di sekolah menengah atas. Analisis isi digunakan untuk menganalisis jenis gambar yang menjelaskan warisan budaya. Hasil penelitian menunjukkan bahwa 163 gambar yang ditampillan, 84 berupa foto, 14 gambar digital, sembilan brosur, 35 iklan, empat brosur, sembilan formulir, 16 peribahasa, dan satu teka-teki. Bias budaya dan stereotip belum terdeteksi dalam gambar yang disajikan di kedua buku teks dengan judul yang sama untuk siswa kelas 10 dan 11 SMA. Gambar yang disajikan sesuai untuk siswa di tingkat sekolah menengah atas. Visual yang disajikan memiliki nilai estetika dan bertujuan agar siswa mengenal berbagai unsur budaya Indonesia yang disajikan dalam buku teks tersebut. Guru dan siswa yang menggunakan buku terbitan PT Grafindo Medika Pratama sebagai sumber belajar, penelitian ini dapat membantu dalam memetakan dan mendeskripsikan jenis budaya yang disajikan dalam buku teks.Kata Kunci: Indonesia, budaya, warisan, gambar, bukuteks,